1974
DOI: 10.1111/j.1476-5381.1974.tb08559.x
|View full text |Cite
|
Sign up to set email alerts
|

THE EFFECT OF INDOMETHACIN ON THE CARDIOVASCULAR AND METABOLIC RESPONSES TO E. coli ENDOTOXIN IN THE CAT

Abstract: I The response of pentobarbitone-anaesthetized cats to the intravenous administration of E. coli endotoxin (2 mg/kg) consisted of acute pulmonary vasoconstriction (3-5 min after the injection) and a secondary shock phase characterized by delayed systemic hypotension, decreased central venous pressure and cardiac output, and metabolic acidosis with arterial lactate levels three to four times normal. Only one of 25 animals survived 6 hours. 2 Indomethacin (10 mg/kg), administered intravenously 30 min before the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
46
3

Year Published

1976
1976
1994
1994

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(52 citation statements)
references
References 15 publications
3
46
3
Order By: Relevance
“…The two most obvious vasodilator candidates are nitric oxide (NO) and prostanoids. Whilst we have no direct evidence regarding the activity of cyclo-oxygenase under our conditions, it is known that prostanoids are involved in endotoxaemia (Parratt & Sturgess, 1974;Herman & Vane, 1976;Wise et al, 1980;Myers et al, 1993). However, since prostaglandin E2 (PGE2) causes renal vasoconstriction in the rat (Gerber & Nies, 1979;Quilley et al, 1989), and PGI2 causes mesenteric vasodilatation with little effect on renal blood flow in conscious rats (Gardiner et al, unpublished observations), the haemodynamic changes noted must have involved other prostanoids, if the latter were involved at all.…”
Section: Discussionmentioning
confidence: 81%
“…The two most obvious vasodilator candidates are nitric oxide (NO) and prostanoids. Whilst we have no direct evidence regarding the activity of cyclo-oxygenase under our conditions, it is known that prostanoids are involved in endotoxaemia (Parratt & Sturgess, 1974;Herman & Vane, 1976;Wise et al, 1980;Myers et al, 1993). However, since prostaglandin E2 (PGE2) causes renal vasoconstriction in the rat (Gerber & Nies, 1979;Quilley et al, 1989), and PGI2 causes mesenteric vasodilatation with little effect on renal blood flow in conscious rats (Gardiner et al, unpublished observations), the haemodynamic changes noted must have involved other prostanoids, if the latter were involved at all.…”
Section: Discussionmentioning
confidence: 81%
“…Regardless of the precise mechanism of action, indomethacin has been shown to have a beneficial effect during different shock states in various animal species including endotoxic shock (Parratt & Sturgess, 1974;1975;Fletcher & Ramwell, 1977;Fletcher, 1982;Mozes et al, 1989). However, one should keep in mind, that this beneficial effect was transient in the present study.…”
Section: Indomethacin Treatmentmentioning
confidence: 99%
“…Indomethacin is effective in improving survival with concomitant decrease in cyclooxygenase enzyme products in endotoxin-induced shock in rats (Ball et al, 1986). Furthermore, indomethacin is able to prevent the initial rapid drop in arterial blood pressure after endotoxin challenge in cats (Parratt & Sturgess, 1974;1975). Additionally, indomethacin has been found to reduce the hypotensive and toxic effect of TNF (Kettelhut et al, 1987;Goto et al, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…It also delayed the onset of the secondary shock phase, which is characterized in this species by systemic hypotension, a reduction in cardiac output and an increasingly severe metabolic acidosis (Parratt, 1973). However, one problem with using indomethacin in this experimental model is that it can cause substantial myocardial depression (Parratt & Sturgess, 1974). Although it is not known whether the pulmonary changes that occur in septic shock are modified by drugs like indomethacin it seemed worthwhile exploring the effect of other antipyretic-analgesic drugs on the pulmonary effects of endotoxin in the cat; such drugs might be more effective than indomethacin and cause less myocardial depression, an important consideration since myocardial function is often depressed in septic shock (Siegel & Fabian, 1967).…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study (Parratt & Sturgess, 1974) we showed that indomethacin, in a single intravenous dose of 10 mg/kg, prevented the pulmonary hypertension and oedema that follows the administration of E. coli endotoxin in the cat. It also delayed the onset of the secondary shock phase, which is characterized in this species by systemic hypotension, a reduction in cardiac output and an increasingly severe metabolic acidosis (Parratt, 1973).…”
Section: Introductionmentioning
confidence: 99%